The transition between a poroma and a porocarcinoma evidenced by the dermoscopy - Juliana Uchiyama; Márcio Martins Lobo Jardim; Neusa Yuriko Sakai Valente; Maria Fernanda Vieira Cunha Camargo (Sociedade Brasileira de Dermatologia, 2019)
Abstract Eccrine porocarcinoma (EPC) is a rare malignant skin tumor. The dermoscopy of invasive EPC reveals focal presence of whitish-pink, structureless areas surrounded by pinkish-white halos. In an eccrine poroma (EP), such areas present diffuse distribution in the "frog- eggs" pattern. We reported an EPC in situ that presents a transitional dermoscopy pattern between EP and invasive EPC. We found a diffuse distribution; whitish-pink, structureless areas surrounded by pinkish-white halos; a central exulceration and a polymorphic vascular pattern.